2015
DOI: 10.5152/ucd.2015.2828
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic stent placement in the management of malignant colonic obstruction: Experiences from two centers

Abstract: Objective: Intestinal obstruction due to colorectal tumors requires immediate surgical decompression. Endoscopic stent placement for acute malignant colonic obstruction is gaining widespread acceptance as an alternative to emergency surgery. Our aim in this study was to evaluate the success and complication rates of endoscopic stenting for malignant colonic obstruction. Material and Methods:Patients with acute malignant colonic obstruction who underwent endoscopic stenting between 2011-2014 were retrospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…The 33.3% of the patients were stented for palliation. The mean follow-up period of these cases was 8 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) months, and the patients were lost because of their preexisting diseases. Any complication did not develop during stent placement for bridging to surgery, and any case of mortality was not observed due to stent application.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 33.3% of the patients were stented for palliation. The mean follow-up period of these cases was 8 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) months, and the patients were lost because of their preexisting diseases. Any complication did not develop during stent placement for bridging to surgery, and any case of mortality was not observed due to stent application.…”
Section: Resultsmentioning
confidence: 99%
“…[9,10] In patients with poor general condition or in the presence of widespread disease, such as peritoneal carcinomatosis, irresectable metastasis, and irresectable T4 tumors, SEMS has been widely accepted as an alternative method to emergency surgery to convert emergency state to elective state in cases of resectable tumors so as to eliminate the disadvantages that may be caused by emergency operation or with the purpose of palliation. [11,12] In SEMS application, owing to technical reasons, such as bowel contamination, non-visualization of the tumor, and failure to negotiate the guidewire or stent, success may not be achieved. In a study with a median follow-up period of 106 (68-288) days, technical and clinical success rates of SEMS were reported to be 96.2% and 92%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although the literature indicates that it is safe, certain conditions must be met for stent placement in colonoscopic perforations. Generally, these conditions are related to the hospital facilities, including the availability of an experienced endoscopist and associated assistant team and the availability of the proper stent and equipment when required (40).…”
Section: Discussionmentioning
confidence: 99%
“…164 With respect to colonic SEMS, a large prospective series of 513 patients and 6 retrospective studies found the risk of clinically relevant haemorrhage within 7 days to be 0%. [165][166][167][168][169][170][171][172][173][174] A systematic review identifying 40 studies on SEMS for the management of emergency malignant large bowel obstruction identified 9 studies reporting on clinical relevant bleeding which occurred in 0.5% (8 out of 1474 patients). 175 We have considered endoscopic stenting at all sites in the GI tract to be low risk for haemorrhage within 7 days.…”
Section: Endoscopic Stentingmentioning
confidence: 99%